Comparative plastome analysis of Blumea, with implications for genome evolution and phylogeny of Asteroideae. Issue 12 (6th May 2021) - Abdullah,; Mehmood, Furrukh; Rahim, Abdur; Heidari, Parviz; Ahmed, Ibrar; Poczai, Péter
Abstract: The genus Blumea (Asteroideae, Asteraceae) comprises about 100 species, including herbs, shrubs, and small trees. Previous studies have been unable to resolve taxonomic issues and the phylogeny of the genus Blumea due to the low polymorphism of molecular markers. Therefore, suitable polymorphic regions need to be identified. Here, we de novo assembled plastomes of the three Blumea species B . oxyodonta, B. tenella, and B. balsamifera and compared them with 26 other species of Asteroideae after correction of annotations. These species have quadripartite plastomes with similar gene content, genome organization, and inverted repeat contraction and expansion comprising 113 genes, including 80 protein‐coding, 29 transfer RNA, and 4 ribosomal RNA genes. The comparative analysis of codon usage, amino acid frequency, microsatellite repeats, oligonucleotide repeats, and transition and transversion substitutions has revealed high resemblance among the newly assembled species of Blumea . We identified 10 highly polymorphic regions with nucleotide diversity above 0.02, including rps 16‐ trn Q, ycf 1, ndh F‐ rpl 32, pet N‐ psb M, and rpl 32‐ trn L, and they may be suitable for the development of robust, authentic, and cost‐effective markers for barcoding and inference of the phylogeny of the genus Blumea . Among these highly polymorphic regions, five regions also co‐occurred with oligonucleotide repeats and support use of repeats as a proxy for the identification of polymorphic loci. The phylogenetic analysis revealed a close relationship between Blumea and Pluchea within the tribe Inuleae. At tribe level, our phylogeny supports a sister relationship between Astereae and Anthemideae rooted as Gnaphalieae, Calenduleae, and Senecioneae. These results are contradictory to recent studies which reported a sister relationship between "Senecioneae and Anthemideae" and "Astereae and Gnaphalieae" or a sister relationship between Astereae and Gnaphalieae rooted as Calenduleae, Anthemideae, and then Senecioneae using nuclear genome sequences. The conflicting phylogenetic signals observed at the tribal level between plastidt and nuclear genome data require further investigation. Abstract : Our study provides insight into plastome structure evolution of the genus Blumea and the subfamily Asteroideae (Asteraceae). Previously, the phylogeny of Blumea could not be resolved due to lack of knowledge of suitable polymorphic loci. Based on comparative genomics, we report suitable polymorphic loci which are also co‐occur with repeats and support the role of repeats as proxy for identification of polymorphic loci. The conflicting phylogenetic signals observed at tribe level between plastome and nuclear genome data may be due to reticulate and abrupt evolution which require further investigation. ​